THE EFFECTIVENESS OF ENGLISH SONGS FOR TEACHING ENGLISH TO YOUNG LEARNERS - Hanif, Muhammad Syafa (Universitas Muria Kudus, 2024)
This study aims to analyze the differences in students' vocabulary pronunciation skills with English songs as media. The choice of this topic was based on one of the problems that students often face, namely vocabulary pronunciation skills. These abilities are some of the four important skills in English that must be mastered.Researchers believe that people who learn English must master vocabulary pronunciation. Using songs in the learning process is one of the media to teach children to master vocabulary pronunciation. The participants in this study were fourth-grade students at SD 2 Hadipolo. The intended class is the fourth grade which has 18 students.This research method is pre-experimental. Data was collected through pre-test and post-test. The researcher conducted a pre-test and then the students listened to the song for treatment. And the last step is the post-test.Based on t0 being greater than the t-table, (10.238 2.110), it means that H0 is rejected. The researcher concluded that there was a significant difference between the pre-test and post-test. The improvement of students can be seen from their average score from 53.3 in the pre-test to 78.88 in the post-test. It can be concluded that English songs are Effective as a tool for teaching vocabulary and pronunciation to fourth-grade students at SD 2 Hadipolo in the 2022/2023 academic year.The researcher suggests the teacher use songs that meet the material. The researcher suggests to the students keep learning while listening to songs to add more knowledge. The other researcher can benefit from this study in a number of ways and use it as extra research material in the future.